The relationship between perceived self-efficacy and contraceptive behaviors among Iranian women referring to health centers in Mashad in order to decrease unwanted pregnancies - N Peyman; A Heidarnia; F Ghofranipour; A Kazemnejad; GH Khodaee; F Amin Shokravi (JRI, 2007)
Introduction: Unwanted pregnancy remains a major public health concern. In Iran, 8.7% of women of reproductive age (15-49) have an unwanted pregnancy during use of a reversible method of contraception, and 5.6% of these pregnancies occur among Oral Contraceptive (OC) users. OC use is the most popular and widely used method among Iranian women. The recent Iran Demogra-phic and Health Survey (IDHS) reported that only half (51.5%) of OC users take it correctly. The aim of this study was to investigate the influence of the women’s self-efficacy on their oral contra-ceptive performance. Materials & Methods: This study was a cross-sectional survey on oral contraceptives that investi-gated contraceptive behavior based on steps to behavior change (SBC) model and self efficacy theory of OC users in Iran. The survey was conducted from July 2005 to May 2006 in family planning clinics of Mashad Health Centers. Three hundred and fifty two OC users were interview-ed. The collected data were analyzed by SPSS software. Statistical methods such as descriptive analysis, spearman correlation and multiple regressions were employed. Results: Family planning self-efficacy was significantly related to knowledge, approval, intention, practice and advocacy, among which, intention and advocacy had the highest correlation and predictability power. Standard multiple regression analysis revealed that this model had worked extremely well. Indeed, the independent variables accounted for 54.5% of the variance in intention. Conclusion: This study confirms that the hypothesis of improving family planning self-efficacy can be effective in consistent and correct use of oral contraceptive pills and it can produce positive outcomes. It is suggested that the findings of present study be used as a basis for interventions designed to enhance better performance in the concerned area.
Keywords: Family planning, Oral contraceptive pill, Iranian women, Health centers, Self-efficacy, Steps to behavior change model, Unwanted pregnancy